Economic Considerations for Moving beyond the Kato-Katz Technique for Diagnosing Intestinal Parasites As We Move Towards Elimination. Issue 6 (June 2017) - Turner, Hugo C.; Bettis, Alison A.; Dunn, Julia C.; Whitton, Jane M.; Hollingsworth, T. Déirdre; Fleming, Fiona M.; Anderson, Roy M.
Abstract : While the need for more sensitive diagnostics for intestinal helminths is well known, the cost of developing and implementing new tests is considered relatively high compared to the Kato-Katz technique. Here, we review the reported costs of performing the Kato-Katz technique. We also outline several economic arguments we believe highlight the need for further investment in alternative diagnostics, and considerations that should be made when comparing their costs. In our opinion, we highlight that, without new diagnostic methods, it will be difficult for policy makers to make the most cost-effective decisions and that the potentially higher unit costs of new methods can be outweighed by the long-term programmatic benefits they have (such as the ability to detect the interruption of transmission). Trends: The Kato-Katz technique is a widespread tool in intestinal helminth epidemiological surveys. It is used in monitoring and evaluation programmes to investigate the prevalence and geographical distribution of soil-transmitted helminth and Schistosoma mansoni infections – determining the WHO treatment strategy to be used. While the need for more sensitive diagnostic methods for these intestinal parasites has been identified, the cost of developing and employing new and potentially more rapid tests is considered relatively expensive, particularly compared to the Kato-Katz technique (which is often referred to as cheap). Consequently, this area has suffered from a lack of investment. The actual cost of using the Kato-Katz technique is higher and more variable than is often being assumed, and it is difficult to implement at a large scale.